Analisis Dampak Reklamasi Pantai Manado dari Sudut Pandang Hak Asasi Manusia - Hikmah Zougira; Nanik Prasetyoningsih (Universitas Muhammadiyah Yogyakarta, 2023)
The development of coastal areas using reclamation is an activity that is quite active in the city of Manado. Many coastal communities do not agree with reclamation because this activity is considered to only bring problems for them. loss of sea area as a place of livelihood is the core problem of reclamation, as a result, this has an impact on the economic decline of coastal communities. The purpose of this study regarding Manado Beach reclamation is to examine it from a human rights perspective. This research method is normative-empirical. Based on the results of Manado reclamation research, it has violated the human rights inherent in fishermen, this violates the Republic of Indonesia Law Article 28, Law 39/1999 Article 1 (1), Law No 1/2014 in conjunction with Law No 27/2007 Article 1 (31), Law No 27/2007 Article 23 (5), Article 34 (2), Article 63 (1), Permen No 25/PERMEN-KP/2019 Article 16 (1) and Manado City Regional Regulation No 1/2017 Article 23(2). As a result of this behavior, the perpetrators can be tried with sanctions written in the Minister of Maritime Affairs and Fisheries Regulation No. 25/PERMEN-KP/2019 Article 17 (1), (2), (3) in general, the holder of a reclamation permit is obliged to provide compensation to people who affected by reclamation activities.